"When I suffer from fever, I eat mangos." Determinants of health-seeking beliefs and behaviors of rural older women in Sylhet, Bangladesh. (2nd January 2023) - Hamiduzzaman, Mohammad; De Bellis, Anita; Abigail, Wendy; Harrington, Ann; Fletcher, Amber
ABSTRACT: Poverty, poor living conditions, religious values and norms, lack of education, and gender discrimination influence the beliefs and behaviors of rural older women in many low-income countries. This paper aims to report the socio-ecological determinants of health-seeking beliefs and behaviors of rural older women in North-eastern Bangladesh and how these behaviors impact their recognition within the setting. It involved semi-structured interviews with 25 older women and 11 healthcare professionals. The findings revealed various determinants at the personal level (awareness of illness, mistrust toward medical treatment, self-treatment, and religious values and norms), the interpersonal level (isolation in family and communication with clinicians), community level (community perception of aging, neighboring and community organizations), and in the sphere of human rights (care affordability, social safety-net coverage and national policy). Four core determinants (poverty, education, gender and religiosity) were intertwined in shaping beliefs and behaviors.